2011
DOI: 10.2478/v10168-011-0017-9
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Sound-Engineering

Abstract: Organologic and campanologic acoustical problems due to applications to sacral objects are characterized on ground of numerous reviewed publications and engineering reports. Participation of several involved research centres, mostly Polish, at solving these problems is evaluated. Some desirable future developments are indicated. Appendices bring examples of documentation on selected investigated objects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The carillon is a collection of pitched bells that is played with a keyboard. Bells have inharmonic spectra, and we might expect these inharmonic spectra to induce substantial deviations in consonance properties from standard harmonic instruments, as has been stated in Preprint (March 2024) _________________________________________________________________________________ musicians' writings about the carillon (Archer, 1937) as well as previous modelling studies (Sethares, 2005) but not yet established empirically (though see Budzyński & Sankiewicz, 2014 for a preliminary investigation).…”
Section: Introductionmentioning
confidence: 87%
“…The carillon is a collection of pitched bells that is played with a keyboard. Bells have inharmonic spectra, and we might expect these inharmonic spectra to induce substantial deviations in consonance properties from standard harmonic instruments, as has been stated in Preprint (March 2024) _________________________________________________________________________________ musicians' writings about the carillon (Archer, 1937) as well as previous modelling studies (Sethares, 2005) but not yet established empirically (though see Budzyński & Sankiewicz, 2014 for a preliminary investigation).…”
Section: Introductionmentioning
confidence: 87%
“…From that moment, and in the context of where the congregation should listen and understand the liturgical act, this architect considered the acoustic problem as a constant to be addressed and resolved in his religious architecture. The importance of these facts in the acoustics of churches and the need for its study has been suggested by other authors (Budzyński, 2011).…”
Section: Introductionmentioning
confidence: 98%